Difficult airway communication between anaesthetists and general practitioners. Issue 1 (February 2013) - Wilkes, M; Beattie, C; Gardner, C; McNarry, AF
Background and aims: Advance warning of patients who are difficult to intubate may prevent an airway catastrophe but relies on effective communication between specialties. Anaesthetists aim to inform general practitioners whenever a difficult airway is encountered and expect general practitioners to include this information in subsequent referrals. We investigated how anaesthetists communicated with general practitioners, their knowledge of the Read Code (used by general practitioner computer systems) for difficult tracheal intubation, and how likely general practitioners were to pass the information on. Methods and results: We surveyed 631 consultant anaesthetists and 217 general practitioners. We found only 125 (20%) anaesthetists consistently wrote difficult airway letters to general practitioners. Only 20 (3%) knew the Read Code for difficult intubation (SP2y3), although 454 (72%) thought it to be useful. Most general practitioners (212, 98%) thought airway information to be important, but only half receiving a difficult airway communication forwarded it on. General practitioners recommended including the Read Code SP2y3 and labelling it 'high priority', ensuring that 'Difficult Tracheal Intubation' would be listed in the Emergency Care Summary generated for hospital referrals. Conclusion: Communication between anaesthetists and general practitioners is currently poor, but could be improved by simplifying difficult airway letters and including the SP2y3 code and a statement of priority.